Professor Faizal shared ionosphere research in Malaysia - UMP, PNC
Professor Ir.Dr.Ahmad Faizal Mohd Zain from the Faculty of Manufacturing Engineering Universiti Malaysia Pahang (UMP) shared his expertise relating to ionosphere in a public academic talk titles, 'Electrons Making Waves in the Sky: The ionosphere and Us' at the faculty's lecture hall 1 in UMP Pekan on September 19.